Religious Tolerance Model in Salatiga: Analysis of the Implementation of Religious Moderation Concept in a Multicultural City - Nugroho, Muhammad Aji (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
This study examines the model of religious tolerance in Salatiga, a city known for its religious diversity, focusing on the role of Islam in promoting religious moderation. Salatiga has been recognized as one of Indonesia's most tolerant cities due to strong religious awareness, supportive government policies, and the active role of religious leaders in fostering interfaith harmony. The concept of religious moderation in Salatiga emphasizes not only passive acceptance of differences but also active efforts to create peace and mutual support. However, challenges such as social tensions and identity politics still persist. This research, using a qualitative approach with case study methodology, explores the implementation of religious tolerance in Salatiga through in-depth interviews, documents, and participatory observations. The findings highlight key strategies for maintaining tolerance, including the involvement of religious leaders, optimizing local wisdom, implementing social justice-based government regulations, promoting inclusive religious understanding, and integrating tolerance into local traditions. The study concludes that while Salatiga serves as a strong example of religious tolerance, continuous efforts are needed to foster peace and strengthen social cohesion in a pluralistic society.